Synthesis, Pharmacological Activity and Uses of Chalcone Compounds: A Review - Taresh, Ban H. (Scientific Journal of Medical Research, 2022)
Chalcones as a chemical compound has piqued attention in a variety of sectors (academia besides and industry). Many chalcones derivatives are now used to treat viral infections, cardiovascular infections, parasite toxicity, pain, gastritis, stomach tumors, and food flavors and cosmetic formulation elements. However, much of the chalcones' medical potential is still untapped. This survey aims to discuss the importance of chalcones, their applications, preparations, and reactions, as well as scientists involved in the pharmacological screening of formatted chalcones, studying the importance of chalcones, and preparing pharmacologically active chalcones with biological activities. Although naturally occurring chalcones have long been used in traditional medicine, recent scientific breakthroughs have revealed that these chemicals exhibit a wide spectrum of biological activity in a variety of animals. It is possible to obtain these natural chemicals. Chalcones are chemical compounds having a wide range of biological activity used in agriculture to control weeds and undesired pests.